The emerging dimensions of SAARC - Muni, S. D.; Institute of South Asian Studies (Singapore) (New Delhi : Foundation Books, 2010)
Papers presented at a series of seminars organized by Institute of South Asian Studies, National University of Singapore.
Includes bibliographical references and index.
Keywords: South Asian Association for Regional Cooperation